“Husband, father, coward, killer”: The discursive reproduction of racial inequality in media accounts of mass shooters - Bridges, Tristan; Tober, Tara Leigh; Brazzell, Melanie; Chatterjee, Maya (Frontiers in Psychology, 2022)
Relying on more expansive criteria for defining “mass shootings” than much existing research, we examine a subset of a unique dataset incorporating 7,048 news documents covering 2,170 shootings in the U.S. between 2013 and 2019. We analyze the descriptive language used to describe incidents and perpetrators and discover significant racial disparities in representation. This research enables a critical examination of the explanatory frames utilized by news media to tell the public who mass shooters are and journalistic attempts to explain why they occur. Data were analyzed utilizing a mixed methods approach, relying on content analysis to inductively code emergent categories of descriptions of shooters and binary logistic regressions to analyze the preponderance of descriptive categories when comparing news articles reporting on shootings committed by differently racialized shooters. Our results confirm some recent research showing that mass shooters racialized as white are more likely to be described with kind and compassionate language. With our larger sample, however, we also find that mass shooters racialized as white are additionally more likely to be described with negative language as “bad” or “evil” in comparison to shooters of color. We discuss how these data demonstrate that media reports present a more complex picture of white mass shooters for the public than shooters of color.